2016
DOI: 10.1074/jbc.m116.717405
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Concerted RNA-DNA Primer Synthesis by the Human Primosome

Abstract: The human primosome, a 340-kilodalton complex of primase and DNA polymerase ␣ (Pol␣), synthesizes chimeric RNA-DNA primers to be extended by replicative DNA polymerases ␦ and ⑀. The intricate mechanism of concerted primer synthesis by two catalytic centers was an enigma for over three decades. Here we report the crystal structures of two key complexes, the human primosome and the C-terminal domain of the primase large subunit (p58 C ) with bound DNA/RNA duplex. These structures, along with analysis of primase/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
233
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(254 citation statements)
references
References 58 publications
20
233
1
Order By: Relevance
“…Both the 5′-triphosphate of a primer and the 3′-overhang of a template are critical for DNA:RNA binding by p58C and primase (4, 6) (Fig. 1C, highlighted in blue).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the 5′-triphosphate of a primer and the 3′-overhang of a template are critical for DNA:RNA binding by p58C and primase (4, 6) (Fig. 1C, highlighted in blue).…”
Section: Main Textmentioning
confidence: 99%
“…In the conserved p58C/substrate complex structure Y345 interacts with the γ-phosphate of the initiating NTP (Fig. 1B) (4), which is rather sensitive to the binding environment (8,9). For example, mutation of Arg306 analog in yeast primase, which makes two contacts with initiating NTP (4), completely abrogates de novo RNA synthesis (9).…”
Section: Main Textmentioning
confidence: 99%
“…tured NTD and the exonuclease and polymerase domains, but lacks the unstructured N-terminal tail and its CTD. The CTD of Pol ␣ serves as a structural model for this domain in the other B-family DNA polymerases (19,20).…”
Section: Pol3) or Pbl326 (Trp1 Pol3-69) And Pbl249 (Leu2 Pol30 Or mentioning
confidence: 99%
“…However, biochemical studies of Pol ␦ and Pol have shown that the C-terminal 4-cysteine lobe ligands an iron-sulfur cluster in the 2ϩ coordination state (21,22). The CTDs of Pol ␣, Pol ␦, and Pol ⑀ each bind a distinct B subunit, called Pol12, Pol31, and Dpb2, respectively, in budding yeast (19,21,23), and these B subunits show both sequence and structural conservation (19,20,24,25). Pol has appropriated the B subunit from Pol ␦ to elaborate its own four-subunit assembly (Rev3-Rev7-Pol31-Pol32) (22, 26 -28).…”
mentioning
confidence: 99%
See 1 more Smart Citation